Anterior Reduction and Fusion of Cervical Facet Dislocations. Issue 2 (14th March 2018) - Theodotou, Christian B; Ghobrial, George M; Middleton, Andrew L; Wang, Michael Y; Levi, Allan D
Abstract: BACKGROUND: Cervical facet dislocations are among the most common traumatic spinal injuries. Posterior, anterior, and combined surgical approaches have been described and are widely debated. OBJECTIVE: To demonstrate efficacy in anterior-only surgical management for subaxial cervical facet dislocations. METHODS: A consistent surgical algorithm for cervical facet dislocation was applied over a 19-yr period and analyzed retrospectively in adults with acute unilateral or bilateral facet dislocation of the subaxial cervical spine. The primary endpoint was maintenance of early cervical alignment. The need for additional posterior instrumented fusion was determined. RESULTS: A database search identified 96 patients (mean age = 37.9, range = 14-74 yr, 68 (70%) male. The most common affected levels were C4-C5 (30), C5-C6 (29), and C6-C7 (30). Bilateral dislocation occurred in 51 patients (53%). Seventy-eight (81%) patients had neurological deficits, 31 (32%) being complete (Abbreviated Injury Score A) spinal cord injuries. Preoperative closed reduction was attempted in 60 (63%) patients, with 33 (55%) achieving satisfactory alignment. After anterior cervical discectomy, reduction, allograft placement, and instrumentation, a total of 92 (96%) patients had achieved satisfactory realignment. Median time to surgery was 13.27 h. Eight (8%) patients required posterior fixation due to intraoperative determination of incomplete realignment (4; 4%) and development of early progressive deformity (4; 4%). Mean follow-up was 4.5 mo (range 0.5-24 mo) with 33 (34%) patients lost to follow-up. CONCLUSION: Anterior approaches are viable for reduction and stabilization of cervical facet dislocations. Further prospective studies are required to evaluate clinical and long-term success.